HUBUNGAN KEMAMPUAN APARATUR DAN KOORDINASI DENGAN KUALITAS PELAYANAN PUBLIK PADA KANTOR KECAMATAN HOLONG KABUPATEN BALANGAN - Erna Suriyani (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
This study aims to find Apparatus ability Relations and Coordination with Quality of Public Services at the District Office Halong BalanganThis type of research used in this study is the type eksplanatory, approach used in this study is the quantitative approach. To prove the relationship of work ability, coordination with the quality of service, will be analyzed using Chi Square models.Measuring the quality of service in this study using the opinion of Parasuraman, Zeithaml, and Berry (Tjiptono, 2004: 132) Levince in Ratminto (2005: 175). Factors affecting the quality of service inferred from Moenir opinion, The Liang Gie Fan Info and theory The Triangle of Service Quality proposed by Morgan and MurgatroydThe findings of the research show that in fact the ability of the apparatus to the quality of public services in the dimensions of Reliability (Reliability), responsiveness (responsiveness), assurance (Confidence), Empathy (Attention) and Tangibles (tangible) at the district office Halong Balangan, at significant level 1 % proved no hungan, while the significant level of 5% proved to be no relationship.Coordination with the quality of public services in realiability dimensions (Reliability) and Assurance (Confidence), at the district office district Halong good Balangan Significant level of 1% and 5% proved to be no correlation, while coordinating with the quality of public services in the dimension Responsiveness (power Response). Empathy (Attention) Tangibles (tangible) at the district office district Halong Balangan On Significant level of 1% proved to be no relationship While the extent of 5% Significant proven there is a relationship.Based on the research finding, then things need to be advised to get attention in order to improve the quality of public services are as follows: